2019
DOI: 10.1186/s12893-019-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery versus muscle-sparing thoracotomy for non-small cell lung cancer: a systematic review and meta-analysis

Abstract: Background It has been widely accepted that video-assisted thoracoscopic surgery (VATS) lobectomy is superior to conventional open thoracotomy lobectomy in many aspects. However, the direct comparison between VATS and Muscle-sparing thoracotomy (MST) has not been widely conducted. We aimed to compare the perioperative outcomes in non-small cell lung cancer (NSCLC) patients following VATS and MST. Methods PubMed, EMBASE, the Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
(44 reference statements)
0
18
0
5
Order By: Relevance
“…This results in longer operating times and higher intraoperative complication rates during that learning period (6). Its use in oncological procedures was a controversial subject until proven otherwise (8,(19)(20)(21)(22). With experience, operation durations tend to be lower with less intraoperative complications (8,19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in longer operating times and higher intraoperative complication rates during that learning period (6). Its use in oncological procedures was a controversial subject until proven otherwise (8,(19)(20)(21)(22). With experience, operation durations tend to be lower with less intraoperative complications (8,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Its use in oncological procedures was a controversial subject until proven otherwise (8,(19)(20)(21)(22). With experience, operation durations tend to be lower with less intraoperative complications (8,19,20). Recent studies report fewer postoperative complications, shorter hospital stay, and shorter chest tube duration without compromising oncological outcomes in VATS (8,19,23).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between thoracoscopy and thoracotomy was also studied in a recent meta-analysis by Wang et al, reviewing the most reliable evidence (29). The pooled analysis of 10 studies and 1,514 patients showed a significant reduction of almost 46% in the incidence of total postoperative complications (odds ratio 0.54, P<0.0001) using VATS.…”
Section: Video-assisted Thoracoscopic Lobectomy Versus Open Lobectomy: Upfront or Post Neoadjuvant Therapymentioning
confidence: 99%
“…Thoracotomy is still the main approach to perform lobectomy for early stage NSCLC: between 2010 and 2012, 67% of lobectomies were performed by open thoracotomy, 26% by VATS, and 7% by RATS, as registered in the USA nationwide cancer database [16] . VATS for early stage NSCLC is now well accepted, with better short-term outcomes [17,18] [ Table 1]. With VATS, a fissureless technique is preferred and mediastinal lymph node dissection is done at the end of the procedure.…”
Section: Performing Lobectomy: Common Points and Differences Between mentioning
confidence: 99%